The Gingerbread Man - Daly, Audrey (Ladybird Books Ltd, 1993)
A freshly baked gingerbread man escapes when he is taken out of the oven and eludes a number of pursuers until he meets a clever fox.
Keywords: Juvenile literature-English language-Fiction